The judicial imagination : writing after Nuremberg - Stonebridge, Lyndsey 1965- (Edinburgh Univ. Press, 2011)
Gathering ashes: the judicial imagination in the age of trauma -- 'An event that did not become an experience': Rebecca West's Nuremberg -- The man in the glass booth: Hannah Arendt's irony -- Fiction in Jerusalem: Muriel Spark's idiom of judgement -- 'We refugees': Hannah Arendt and the perplexities of human rights -- 'Creatures of an impossible time': late modernism, human rights and Elizabeth Bowen -- The dark background of difference: love and the refugee in Iris Murdoch